GAMBARAN KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SIDOMULYO KECAMATAN TAMPAN PEKANBARU - Nur Azmi; Darwin Karim; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is a chronic problem (lifelong), is a silent killer with the highest prevalence rates in the whole world. This condition can affect the quality of life of the elderly. This study aims to find out the description of the quality of life of elderly hypertension in the working area of Sidomulyo Public Health Center, Tampan District, Pekanbaru. This study uses a quantitative descriptive design with a cross sectional approach. This study was conducted on 61 respondents using accidental sampling techniques. The measuring instrument used is the WHOQOL-BREF questionnaire sheet which is a questionnaire to measure quality of life that was modified previously and has been tested for validity and reliability. Data analysis used is univariate analysis to see frequency distribution. The results showed that the quality of life was good physical health domain (54.1%), good quality of life in the psychological domain (68.9%), good quality of life in the social domain (60.7%), good quality of life in the environmental domain (54.1% ), the quality of life both the welfare domain (63.9%), the quality of life both the spiritual domain (75.4%), and the quality of life in general shows (54.1%) the respondents have a good quality of life. This study recommends people especially those who have elderly family members to pay more attention to a healthy lifestyle to avoid further complications of hypertension.Keywords: Hypertension, Quality of Life, Elderly